Pembangunan Peta Virtual 3D untuk Gedung K, Gedung H, Gedung I, dan Gedung R di Fakultas Pertanian Universitas Lampung - Admi Syarif; Sintiya Paramitha; Aristoteles; Favorisen Rosyking Lumbanraja (Jurnal Pepadun, 2023)
The University of Lampung conducts routine activities of Introduction to New Student Campus Life (PKKMB) to introduce every building and public facility within the Faculty of Agriculture as well as every building and room inside. New Students and the general public every year. The current state of the COVID-19 pandemic has forced the University of Lampung to carry out learning activities online. Thus making every student activity impossible to do directly. So we need a method of presenting 3D visualization information. By using Multimedia Development Life Cycle (MDLC) system development method, the developed 3D virtual map application can display building layouts and facilities in 3D so that PKKMB activities related to the introduction of existing buildings and public facilities can still be delivered effectively and efficiently. This research was developed through 2 types of testing, namely testing by developers (Alpha) and customer satisfaction (Betha). Alpha testing provides test results. These Applications can operate on various Android with 7.1 to 12 of operating system and also on smartphone with 5.0 to 6.5 inches of screen. These applications can also be operated on smartphones with RAM range in 3GB to 8GB. Respondents stated that the 3D Virtual Map Application for Building K, Building H, Building I , and Building R, Faculty of Agriculture, University of Lampung, had good results with index percentages ranging from 87.5% to 95%.e basics.